Bermudagrass Production in Florida - Y. C. Newman; J.M.B. Vendramini; C. G. Chambliss; F. A. Johnson; M. B. Adjei (EDIS)
This is a minor revision by Y.C. Newman and J.M.B. Vendramini of the 2/2006 version with the same title.